2019
DOI: 10.1055/s-0037-1611855
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Magnetic Iron(III) Nanocatalyst for Ferrier Rearrangements

Abstract: A novel and highly efficient magnetic Fe3O4@C@Fe(III) core–shell catalyst, in which the carbon shell was prepared from lotus leaf, was fabricated. This nanocatalyst was successfully applied in the synthesis of a series of 2,3-unsaturated O-glycosides in excellent yields and with high selectivity, especially in the case of 2-halo O-glycosides, which differ in reactivity from nonsubstituted O-glycosides, but which have scarcely been explored before. Moreover, the catalyst could be easily separated from the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The reaction conditions were mild, and the range of alcoholic substrates was wide, but the reaction was time-consuming and suffered deacylation as well. On the basis of reports in the literature ( Michigami and Hayashi, 2012 ; Chen and Lin, 2013 ; Chen et al, 2017 ; Dong et al, 2019 ), we concluded that the nitro substituent at the C-2 position has a remarkable effect in the sugar ring and that electron-withdrawing groups reduce the electron density of the oxocarbenium intermediate in the normal Ferrier rearrangement. Consequently, the development of a green and broadly adaptive protocol for the synthesis of 2-nitro-2,3-unsaturated glycosides remains a challenge.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The reaction conditions were mild, and the range of alcoholic substrates was wide, but the reaction was time-consuming and suffered deacylation as well. On the basis of reports in the literature ( Michigami and Hayashi, 2012 ; Chen and Lin, 2013 ; Chen et al, 2017 ; Dong et al, 2019 ), we concluded that the nitro substituent at the C-2 position has a remarkable effect in the sugar ring and that electron-withdrawing groups reduce the electron density of the oxocarbenium intermediate in the normal Ferrier rearrangement. Consequently, the development of a green and broadly adaptive protocol for the synthesis of 2-nitro-2,3-unsaturated glycosides remains a challenge.…”
Section: Introductionmentioning
confidence: 68%
“…In addition, we are introducing a nano-magnetic core-shell catalyst into a Ferrier rearrangement of glycals due to their extraordinary noncontact magnetic separation ( Wang et al, 2019 ; Zhang et al, 2021 ). Previously, Fe 3 O 4 @C-SO 3 H and Fe 3 O 4 @C@Fe(Ⅲ) have been studied for the synthesis of O -2,3-unsaturated glycosides ( Zhang et al, 2017 ; Dong et al, 2019 ; Jiang et al, 2020a ). The donors included 3,4,6-tri- O -acetyl-glucal, 3,4,6-tri- O -acetyl-2-haloglucals, and 3,4-di- O -acetyl-L-rhamnal.…”
Section: Introductionmentioning
confidence: 99%
“…Then we tested the reactions with (-)-menthol and cholesterol that were only reported in the literatura for the D-glucose series. [5] Satisfactory results were also obtained, good yields and high anomeric selectivity are reported in all studied cases. We resume the results in Table 1.…”
mentioning
confidence: 66%
“…Several alcohols were added in a Ferrier fashion to D-glucose unsaturated derivatives using a magnetic iron catalyst. [5] In the present work, we investigated the reactivity of 2-iodo-glycals derived from D-glucose and Dgalactose with different nucleophiles. As part of our recent efforts to obtain biologically active glycosyl derivatives [6] at first, we decided to obtain new O-derivatives that were not reported with the methodology previously cited.…”
mentioning
confidence: 99%
“…Initially, we examined a series of iron(III) catalysts: FeCl 3 •6H 2 O/C, FeCl 3 /C, Fe 3 O 4 @C@Fe(III), which have been widely used as efficient catalysts in glycosylation reactions. [19][20][21] As shown in Table 1, product 3g was gained with poor yield, with the formation of more 2,3-unsaturated Ferrier product (yield 42-60%; entries 1-3). Next, a series of commercial Lewis catalysts were screened (entries 4-9).…”
mentioning
confidence: 99%